A Critical Review of the Revision of Law Number 39 of 2008 on State Ministries from the Perspective of the Indonesian Rule of Law and the Principles of Pancasila Democracy - Daulat Nathanael Banjarnahor; Rengga Kusuma Putra; Firinta Togatorop; David Banjarnahor (Jurnal Ilmiah Multidisiplin, 2025)
As a country with a constitution as the highest fundamental law, Indonesia regulates and distributes state functions to state power organs, which are then referred to as State Institutions. One of the state institutions regulated in the constitution is the State Ministry Institution, which is governed by Article 17 paragraph (1) of the 1945 Constitution of the Republic of Indonesia, stating that the President is assisted by State Ministers. Article 17 paragraph (4) regulates that the establishment, amendment, and dissolution of state ministries are governed by law. This then became a polemic, because the People's Consultative Assembly (MPR) of the Republic of Indonesia had agreed to the Revision of Law Number 39 of 2008 on State Ministries, with one of the important points of change being the absence of a limit on the number of ministries, so that the number of ministries formed and established by the President is in accordance with the needs of state administration. The issues raised in this scientific article are: First, How to Critically Review and Analyze the Revision of Law Number 39 of 2008 on State Ministries from the Perspective or Doctrine of the Indonesian Rule of Law and the Principles of Pancasila Democracy, and Second, Whether the Revision of Law Number 39 of 2008 on State Ministries is in accordance with the Perspective or Doctrine of the Indonesian Rule of Law and the Principles of Pancasila Democracy. The research method used to address the issues in this scientific article is the normative legal research method with a conceptual approach. The conclusion drawn from the problem-solving answers is: First, that the Perspective or Doctrine of the Indonesian Rule of Law and the Principles of Pancasila were not used as guidelines and were ignored by the State in the process of Revising Law Number 39 of 2008 on State Ministries, and Second, that the Revision of Law Number 39 of 2008 on State Ministries does not yet align with the Perspective or Doctrine of the Indonesian Rule of Law and the Principles of Pancasila Democracy.